The role of organizational commitment in the relationship between collaborative leadership and teacher performance - Muhammad Shohib; Suhariadi, Fendy; Agustina, Tri Siwi (University of Muhammadiyah Malang, 2024)
Teacher performance significantly determines the quality of education, and various methods are employed to enhance it. Factors influencing teacher performance include personal, organizational, and managerial aspects. This study aims to examine the role of organizational commitment in the relationship between collaborative leadership and teacher performance. Participants in this research were recruited using purposive sampling, and the criteria included permanent teachers with a minimum of 2 years of experience, totaling 195 individuals. This correlational study utilized Leadership Scale, Organizational Commitment Scale, and Teacher Performance Scale to collect data, which were then analyzed through the Hayes Process Model 4. The findings indicate a relationship between collaborative leadership and teacher performance (r=0.759, p<.01) and organizational commitment with teacher performance (r=0.450, p<.01). Commitment serves as a mediator in the relationship between collaborative leadership and teacher performance, with an indirect effect value of 0.047, se=0.018, cl (0.015 – 0.089), confirming all hypotheses in this study. The study shows that teacher performance is influenced by the collaborative leadership style of the school principal mediated by the organizational commitment of the teachers. To enhance teacher performance, school principals can employ a collaborative leadership model and strengthen organizational commitment.